2001
DOI: 10.1039/b103148c
|View full text |Cite
|
Sign up to set email alerts
|

Simple zwitterionic merocyanines as potential NLO chromophores

Abstract: A suite of zwitterionic pyridylidene-based merocyanines that contain no interconnecting p-bridge between the donor and acceptor rings has been synthesised and their second-order NLO properties evaluated largely by semi-empirical computational methods (MOPAC 97/AM1). Contrary to expectation, increasing the degree of inter-ring twist (h), at least up to 55u, in these new pyridylideneazolone chromophores is found to have little or no effect on the figure of merit [mb( 0 )]. An X-ray crystallographic appraisal of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 34 publications
4
24
0
Order By: Relevance
“…Furthermore as the coupling constants observed for the vinylic protons of the conjugated interconnects are of the order of 12e15 Hz this confirms that they are in an all-trans configuration [23]. This is in contrast to our previous observations for zwitterionic compounds such as 1 and 2, where detailed NMR studies showed two isomers to be present and that these were due to rotational isomerisation about the acceptor ring and conjugated interconnect [14]. The absence of such rotamers in the present compounds is likely due to them being far less charge separated in their ground states (confirmed from X-ray crystallographic studies discussed later in the work), than, for example, 1 and 2.…”
Section: Synthesissupporting
confidence: 72%
See 1 more Smart Citation
“…Furthermore as the coupling constants observed for the vinylic protons of the conjugated interconnects are of the order of 12e15 Hz this confirms that they are in an all-trans configuration [23]. This is in contrast to our previous observations for zwitterionic compounds such as 1 and 2, where detailed NMR studies showed two isomers to be present and that these were due to rotational isomerisation about the acceptor ring and conjugated interconnect [14]. The absence of such rotamers in the present compounds is likely due to them being far less charge separated in their ground states (confirmed from X-ray crystallographic studies discussed later in the work), than, for example, 1 and 2.…”
Section: Synthesissupporting
confidence: 72%
“…The methodology used to prepare 7e9 and 11 relies on an approach previously described by us [14] and which utilizes the N-phenylacetamide precursors 4e6 and 10. Reaction of these precursors with 1,1,3-trimethyl-2-methyleneindoline, 3, in alcohol afforded chromophores 7e9 and 11 as colored solids in yields of 36e87%.…”
Section: Synthesismentioning
confidence: 99%
“…Merocyanine compounds 1, 2 and 3 were synthesised according to [13] and MORPIP were synthesised according to [14]. The structures of the compounds are shown in figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…The 3,5-regioselective iodination of 11 with I 2 under reflux conditions gave 2-hydroxy-3,5-diiodopyridine (12) in 95 % yield. [17] The hydroxy group of 12 was then converted into the bromide using phosphorus tribromide (PBr 3 ) at 145°C to afford 2-bromo-3,5-diiodopyridine (6) in 95 % yield. Interestingly, the bromination did not proceed with N-bromosuccinimide (NBS).…”
Section: Resultsmentioning
confidence: 99%